PERAN SERVANT LEADERSHIP TERHADAP PSYCHOLOGICAL WELL BEING DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DI MODERASI OLEH PERCEIVED ORGANIZATION SUPPORT - Astuti, Sri Astia Widia; Anindita, Rina (Jurnal Psikologi : Media Ilmiah Psikologi, 2024)
In facing the uncertainty of business development, service companies depend on their employees' voluntary efforts and competence. The purpose of this research is to explore the relationship between servant leadership, psychological well-being, and organizational citizenship behavior, which is moderated by perceived organizational support in employees who work in labor supply service industry companies in Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek) in September 2023. The 180 data were examined using the Structural Equation Modeling (SEM) data analysis method. Servant leadership can support psychological well-being, servant leadership can positively impact organizational citizenship behavior, psychological well-being supports organizational citizenship behavior, and perceived organizational support does not support the relationship between servant leadership and organizational citizenship behavior. In addition, it was found that psychological well-being can mediate the relationship between servant leadership and organizational citizenship behavior. This research provides managerial implications that superiors with servant leadership can increase psychological well-being; it influences employee organizational citizenship behavior when psychological well-being increases. Thus, the results of this research can be a reference for further research in identifying other factors.